THE RELATIONSHIP BETWEEN KNOWLEDGE ABOUT ANEMIA AND THE CLASSIFICATION OF ANEMIA IN ADOLESCENT GIRLS AT SMAN 2 BENGKULU CITY IN 2023 - Suci Sholihat; Bela Eka Avrini; Elly Wahyuni; Yuniarti Yuniarti; Ratna Dewi (Proceeding B-ICON, 2023)
Anemia is a condition in which the number of red blood cells or the concentration of hemoglobin in them is lower than usual. The global prevalence of anemia in women aged 15-49 years is 29.9%. In 2019, Indonesia ranks 5th (22.331%) of the World Health Organization (WHO, 2021). This study aims to determine the relationship between knowledge and compliance of consumption of blood-added tablets on the incidence of anemia in SMA Negeri 2 Kota Bengkulu. The research design used quantitative research methods with a cross sectional approach. The population in the study was class X students at SMA Negeri 2 Kota Bengkulu totaling 246 people with a sample of 39 people and for sampling in this study were students who had anemia or Hemoglobin < 12 g / dl. Data analysis in research using Chi-Square test. The results of the study found that there was a significant relationship between knowledge about anemia and the classification of anemia in adolescent girls aimed at p-value = 0.003. So there is a relationship between knowledge about anemia and the classification of anemia in adolescent girls at SMA Negeri 2 Kota Bengkulu. It is expected that related health services, researchers, institutions and research sites can conduct counseling/education/health education in order to increase knowledge and compliance with the consumption of blood-added tablets.